Genome-wide association study in primary angle closure glaucoma - Sarfarazi, Mansoor (Annals of Eye Science, 2017)
Before the Human Genome Project, family-based mapping, positional cloning and mutation screening of candidate genes were largely used to ascertain the etiology of a given genetic disease. While this method proved to be very effective for most Mendelian single-gene disorders, it was not efficient for multigenic disorders with unknown genetic etiology. Subsequent advancement in molecular genetics techniques provided an opportunity to screen millions of biological markers in thousands of patients in a relatively short period of time. One rapid technique that is already used in a large number of clinical disorders is genome-wide association study (GWAS). Other screening methods include next-generation exome sequencing, whole-genome sequencing and targeted regional sequencing.